Radiative transfer in stellar and planetary atmospheres - Arévalo, M. J. 1956-; Crivellari, Lucio 1950-; Simón-Díaz, Sergio 1977- (Cambridge University Press, 2020)
Radiative transfer is essential for obtaining information from the spectra of astrophysical objects. This volume provides an overview of the physical and mathematical background of radiative transfer, and its applications to stellar and planetary atmospheres. It covers the phenomenology and physics of early-type and late-type stars, as well as ultra-cool dwarf stars and extrasolar planets. Importantly, it provides a bridge between classical radiative transfer and stellar atmosphere modelling and novel approaches, from both theoretical and computational standpoints. With new fields of application and a dramatic improvement in both observational and computational facilities, it also discusses the future outlook for the field. Chapters are written by eminent researchers from across the astronomical disciplines where radiative transfer is employed. Using the most recent observations, this is a go-to resource for graduate students and researchers in astrophysics.